\color{Red}{Question} \color{Green}{No Spam} if x + y = 9 x – y = 5 then [tex] \frac{

Question

\color{Red}{Question}
\color{Green}{No Spam}
if
x + y = 9
x – y = 5
then
 \frac{ {6( {x}^{2}  +  {y}^{2}) } }{12xy}  = ?

in progress 0
Alaia 4 weeks 2021-10-29T18:47:03+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-29T18:48:51+00:00

    Answer:

    OKKKKKK

    Step-by-step explanation:

    WAIT….BT THEN GIVE THE CODING…BRO…

    0
    2021-10-29T18:48:51+00:00

    Step-by-step explanation:

    x+y=9. ( 1 )

    x-y=5. (2)

    add both of the above equations

    2x=14

    x=7

    y=9-x. ( from eq 2)

    y=9-7. ( x=7)

    y=2

    now,

    6( {x}^{2}  +  {y}^{2} ) \div 12xy

    on dividing numerator and denominator by 6 we get :-

     ({x}^{2}  +  {y}^{2} ) \div 2xy

    insert values of x and y

    ( {7}^{2}  +  {2}^{2} ) \div 2 \times 7 \times 2

    (49 + 4) \div 28

    =53/28

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )